Zionism and Academic Hegemony: The Intersection of Power, Knowledge, and Suppression in the United States Universities - Mehmet Rakipoğlu (Milel ve Nihal)

(untitled)
This paper critically explores the impact of Zionism on academic freedom and knowledge production in U.S. universities. It emphasizes how political lobbying, financial influence, and allegations of antisemitism are strategically employed to establish a cultural hegemony that determines what discourse is acceptable. Based on Michel Foucault's theory of power-knowledge, which posits that knowledge and power are intimately linked and shape one another, and Antonio Gramsci's concept of cultural hegemony, which explains how dominant groups maintain power through ideological means, this study examines how Zionist organizations influence higher education frameworks, research priorities, and public discourse. This manipulation often serves to marginalize, silence, or delegitimize critical perspectives that oppose or challenge Israeli policies and actions, especially those related to the occupation of Palestinian territories and human rights violations. This paper analyzes certain instances highlighting these dynamics, such as the rescinded job offer to Steven Salaita at the University of Illinois following his criticism of Israel’s genocide in Gaza on social media. This case, among others, underscores how Zionist lobbying and donor pressures can directly affect university governance, academic appointments, and freedom of expression within academic settings. Additional examples include the suppression of pro-Palestinian viewpoints and the punishment of students and faculty who advocate for Palestinian rights at various prominent U.S. institutions, which further demonstrate the broader, systematic efforts to control academic discourse. By examining these cases, the study reveals that Zionism's influence is not limited to isolated cases but creates a widespread atmosphere where academic freedom is restricted. Universities meant to be pillars of free thought and critical inquiry, increasingly become arenas where dissent is suppressed and ideological conformity is imposed. This paper highlights the need for a deeper understanding of the mechanisms through which Zionism shapes the intellectual landscape in the U.S., reinforcing power structures that limit open debate and critical scholarship.